Comparison of Hospital Expenditure and Revenue from 6% Hoteling-Eligible Items Over Two Years: A Case Study at Ayatollah Mosavi Zanjan Educational-Medical Center - Hamed Ghavimi; Javad Tajkei; Mahdi Allahyari; Hadi Abbasian (Tehran University of Medical Sciences, 2024)
Background: Drug and hoteling costs account for approximately 30%   of hospital expenses. Therefore, a thorough focus on the efficiency and costs of this sector is of special importance for hospitals, as scrutinizing these costs can enhance service quality. It appears that insurance payments for hoteling services may not be economically viable for government hospitals.  Hence, this study was conducted to examine this assumption. This study aimed to compare allocated hoteling costs with the actual amounts and assess the profit and loss in Ayatollah Mosavi Zanjan Educational-Medical   Center in the years 2018 and 2019. Methods: The number and monetary value of hoteling items delivered from the pharmacy unit to the medical departments (each department separately) during 2018 and 2019 were determined by extracting data from the   HIS system. Additionally, the occupied bed days for each department were identified, and the amount received in rials from insurance organizations (6%   income from hoteling services) was confirmed with the hospital's financial unit. Results: The research findings indicate significant differences in hoteling costs across various hospital departments. CCU, NICU, and Women's   Active Ward were more profitable, while AICU, ICU-OH, and BICU incurred losses. Outpatient cases and certain departments were not covered by hoteling. Non-hoteling items also contributed to hospital losses.   Furthermore, it was revealed that hoteling costs increased by 64% in 2019, while insurance tariffs saw only a 15% increase. Conclusion: The majority of hospital departments running at a loss can have detrimental effects on patient care quality. Therefore, this issue requires oversight from the Ministry of Health, Treatment Deputy, insurance organizations, and hospital management